Archaeological investigation - Carver, M. O. H., author. Link
1 online resource (xlix, 570 pages)
Keywords: "The second edition of Archaeological Investigation is even more ambitious than the first and reaches out into different kinds of archaeological investigation practiced the world over. Including updated theory, aims and methods of field archaeology in the academic and commercial sectors, it to explores the procedures used from discovery to publication. Divided into four parts, Part 1 (Principles) sets the scene for newcomers, showing the axial role of fieldwork in rediscovering the past. Part 2 (In the Field) is aimed at those setting out on their path of exploration. Word pictures on "First day in the Field' and "First day on a dig" provide friendly introductions to the high-tech enterprise that field work has become and how the vital records of discoveries are made. Now fully engaged in the process, the wouldbe archaeologist is ready to take part in the key phase of the investigation: Part 3 (Writing Up). Here all the results of fieldwork are marshalled with a view to analyzing the finds, the use of space and the chronology of what happened at the site. The results are then communicated through museums, the display of sites and above all by publication that presents the discovered objects, buildings and activities and how they contribute to new understanding of the past. Part 4 (Design) is addressed to the fully-fledged field archaeologist ready to participate in their leading action - how to make archaeology happen. It begins with a tour of great projects (Challenges) and then explains the way archaeological projects are devised to break new ground and solve historical and prehistorical problems (Designing Projects). The final chapter discusses the opportunities, pleasures, difficulties and rewards of working as a full-time archaeologist (The Profession). Now with prehistorian Madeleine Hummler as joint author, Archaeological Investigation remains an inspiring, provocative, informative and entertaining book for students and professional, and makes a powerful case for archaeology's benefits and relevance to communities, present and to come"--